Language systems in children with disabilities such as autism - Hamad, Dr.Yara Qadir (Sulaimani Journal for Humanities, 2025)
Autism, or autism spectrum disorder (ASD), is a developmental condition that affects social interaction, communication and behavior. Language and communication development can have a significant impact on people with autism, although the extent of the impact varies greatly from person to person. As a modern condition is constantly developing, due to the advancement of society, technology and information systems, such as the installation of the Internet network, in all cities, towns, and residential units as a basic necessity of human life With autism in particular. In addition to a number of other factors such as: environment, diet, birth type and genetic conditions, this also affects a child's language. Delayed Language Development. Many children with autism experience delays in language development. They may not start speaking at an early age or may have limited ability to form or compose words. In some cases, children may not speak at all and rely on nonverbal forms of communication, such as gestures, facial expressions, or pictures. Sometimes it even causes echolalia. Some children with autism may repeat phrases or words they hear, a phenomenon known as echolalia. This repetition can sometimes be immediate (repeating what was just heard) or delayed (repeating phrases from days or weeks before). It’s often used as a form of communication, even if it doesn’t seem to make sense in the context.
Keywords: Autism; Echolalia; LAD; Language Disorders; Special Education